2000
DOI: 10.1093/pubmed/22.3.435
|View full text |Cite
|
Sign up to set email alerts
|

Urban-rural differences in total hip replacements: the next stage

Abstract: A system of calculating the expected need for a total hip replacements was developed based on the demography and rurality of individual general practices. This system allowed a method of commissioning to be instituted that could significantly reduce in-patient waiting lists for this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 7 publications
1
10
1
Order By: Relevance
“…It is important to emphasize that these results are from a more industrialized country with a relatively advanced transportation infrastructure, so they may not generalize to less industrialized countries. Among industrialized countries with a nationalized health service, one study from Canada showed no rural‐urban difference in hip replacement surgeries (38), but another study from Ireland did demonstrate a higher prevalence of hip replacement surgeries among rural patients (39). Furthermore, while this study explored differences between rural and urban areas, relatively little is known about joint replacement surgeries in suburban populations, an important area for future research.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to emphasize that these results are from a more industrialized country with a relatively advanced transportation infrastructure, so they may not generalize to less industrialized countries. Among industrialized countries with a nationalized health service, one study from Canada showed no rural‐urban difference in hip replacement surgeries (38), but another study from Ireland did demonstrate a higher prevalence of hip replacement surgeries among rural patients (39). Furthermore, while this study explored differences between rural and urban areas, relatively little is known about joint replacement surgeries in suburban populations, an important area for future research.…”
Section: Discussionmentioning
confidence: 99%
“…International studies examining the relationship between rates of joint replacement and socio‐economic status have shown contrasting results 7–9 . The influence of geographical locality on rate of hip and knee arthroplasty has also been shown to vary between countries 10–12 . Although geographical location and socio‐economic status have been identified as barriers to health care in Australia, 1–3 our understanding of whether rates of joint replacement vary with these factors is limited.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] The influence of geographical locality on rate of hip and knee arthroplasty has also been shown to vary between countries. [10][11][12] Although geographical location and socio-economic status have been identified as barriers to health care in Australia, [1][2][3] our understanding of whether rates of joint replacement vary with these factors is limited. The relationships between joint replacement, socio-economic status and geographical locality are likely to be complex and may involve patient-related factors as well as issues relating to the health system.…”
Section: Introductionmentioning
confidence: 99%
“…18 -31 More affluent groups receive greater provision of hip 18,19,29,32,33 and knee replacement. 18 Utilization of hip replacement is higher in rural areas, 26,31,34 and US studies found Whites are more likely to get surgery than other ethnic groups. 19,21,22,27,31,35,36 Many of these studies included all joint operations rather than elective procedures, 19 -24,32,35 -38 some studies focus only on one socio-demographic domain, statistical methods used in some studies are weak, 38 and only one study explored geographical variation in provision.…”
Section: Introductionmentioning
confidence: 99%